2021
DOI: 10.1097/prs.0000000000008217
|View full text |Cite
|
Sign up to set email alerts
|

Incision Location Predicts 30-Day Major Adverse Events after Cosmetic Breast Augmentation: An Analysis of the Tracking Outcomes and Operations for Plastic Surgeons Database

Abstract: Background: Enhanced understanding of early postoperative adverse events will improve patient counseling and preoperative risk modification to decrease complications in implant-based breast augmentation. This study seeks to evaluate the early major adverse events following cosmetic breast augmentation. Methods: A retrospective cohort analysis of the Tracking Outcomes and Operations for Plastic Surgeons database was performed to identify any women undergoing augmentation mammaplasty with an implant between 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Ten publications were identified that compared capsular contracture rates by the incision. [11][12][13][14][15][16][17][18][19][20] Most were retrospective chart reviews. [12][13][14][15][16][17] Three were prospective core studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten publications were identified that compared capsular contracture rates by the incision. [11][12][13][14][15][16][17][18][19][20] Most were retrospective chart reviews. [12][13][14][15][16][17] Three were prospective core studies.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] Most were retrospective chart reviews. [12][13][14][15][16][17] Three were prospective core studies. [18][19][20] A 2005 Danish study found an advantage for an inframammary incision over other approaches, but the sample sizes were small.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the increasing concern from patients about the risks of adverse events following breast augmentation with implants, such as breast implant-associated anaplastic large cell lymphoma and Autoimmune Syndrome Induced by Adjuvants, or simply changes of aesthetic preference, explantation of breast implant surgery became an emerging surgical field [1][2][3]. Evidence suggests that breast explantation effectively improves silicone-related complaints and that the body's self-satisfaction increases with the placement of breast implants and remains increased after their removal [4][5][6].…”
Section: Introductionmentioning
confidence: 99%